2003
DOI: 10.1021/om034039z
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Doubly Bridged Biscyclopentadienes with Molybdenum (Tungsten) Carbonyl

Abstract: Dimolybdenum complexes (X)(Y)[(η5-C5H3)Mo(CO)3]2 [Y = Me2Si, X = Me2C, (CH2)5C, CH2; Y = Ph2Si, X= Me2C] and desilylation products (X)[(η5-C5H4)Mo(CO)3]2 were obtained from the reactions of carbon and silicon doubly bridged biscyclopentadiene ligands (X)(Y)(C5H4)2 with Mo(CO)6 in refluxing xylene. When these ligands reacted with W(CO)6, under similar conditions, in addition to ditungsten complexes (X)(Y)[(η5-C5H3)W(CO)3]2 [X = Me2C; Y = Me2Si, Ph2Si] and desilylation products (X)[(η5-C5H4)W(CO)3]2, a class of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…However, when the reactions of the silyl bridged bis(indene) ligands with Ru 3 (CO) 12 were done in refluxing heptane, decane, decalin, DME or even methyl isobutyl ketone [7], only the desilylation product [C 9 H 7 Ru(CO)] 2 (l-CO) 2 puzzled us a long time. Recently, we found that xylene as solvent for the reaction of silyl or germyl bridged biscyclopentadiene ligands with metal carbonyl can significantly depress the desilylation or degermylation reaction [8]. So xylene was chosen as solvent for the reactions of the silyl bridged bis(indenyl) ligands with Ru 3 (CO) 12 , and the expected products were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…However, when the reactions of the silyl bridged bis(indene) ligands with Ru 3 (CO) 12 were done in refluxing heptane, decane, decalin, DME or even methyl isobutyl ketone [7], only the desilylation product [C 9 H 7 Ru(CO)] 2 (l-CO) 2 puzzled us a long time. Recently, we found that xylene as solvent for the reaction of silyl or germyl bridged biscyclopentadiene ligands with metal carbonyl can significantly depress the desilylation or degermylation reaction [8]. So xylene was chosen as solvent for the reactions of the silyl bridged bis(indenyl) ligands with Ru 3 (CO) 12 , and the expected products were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Melting points are uncorrected. 1 (1), [7] Ph n P(CϵCPh) 3-n (n = 0, 1, 2), [12] Ph 2 P(O)CϵCPh, [19] and FcCϵCH [20] were prepared by literature methods. 131.7,131.6,131.2,131.1,130.4,130.0,129.0,128.9,128.8,128.6,128.1,125.4,123.6,123.5 (Ph) 2 (70 mg, 0.22 mmol) in toluene (30 mL) was heated at reflux for 6 h. During this time the solution turned from deep green to dark brown.…”
Section: Methodsmentioning
confidence: 99%
“…[6] We recently reported that the Me 2 C and Me 2 Si doubly bridged bis(cyclopentadienyl) dinuclear molybdenum carbonyl complex (Me 2 C)(Me 2 Si)[(η 5 -C 5 H 3 )Mo(CO) 3 ] 2 (1) contained an unusually long Mo-Mo bond length, [7] which is a good precursor for the synthesis of other new dinuclear molybdenum complexes, and led to a number of interesting but not always predictable reactions. More recently, our research has focused on the reactions of complex 1 with a series of unsaturated organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Dinuclear metal complexes are often postulated as simple models with which to study the interactions of molecules with metal surfaces [4,5]. For the bridged bis(cyclopentadienyl) metal carbonyl dimers, the nature of a bridge has important effect on the metal-metal bond and its reactivity [6][7][8][9][10][11][12][13][14][15][16]. The single carbon bridged bis(cyclopentadienyl) dinuclear iron, molybdenum and tungsten carbonyl complexes in general have the shortest metal-metal bonds [6][7][8][9][10], while the carbon and silicon doubly bridged bis(cyclopentadienyl) dinuclear iron, molybdenum and tungsten carbonyl complexes have the longest metal-metal bonds [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…For the bridged bis(cyclopentadienyl) metal carbonyl dimers, the nature of a bridge has important effect on the metal-metal bond and its reactivity [6][7][8][9][10][11][12][13][14][15][16]. The single carbon bridged bis(cyclopentadienyl) dinuclear iron, molybdenum and tungsten carbonyl complexes in general have the shortest metal-metal bonds [6][7][8][9][10], while the carbon and silicon doubly bridged bis(cyclopentadienyl) dinuclear iron, molybdenum and tungsten carbonyl complexes have the longest metal-metal bonds [9,11]. As a part of systematic study the structure-reactivity relationship of the bridged bis(cyclopentadienyl) metal carbonyl dimers, especially the effect of the bridge on the metal-metal bond length and its reactivity [9,[11][12][13], in this work a series of ferrocene bridged bis(tetramethylcyclopentadienyl) trinuclear metal carbonyl complexes were synthesized and characterized by X-ray diffraction analysis.…”
Section: Introductionmentioning
confidence: 99%